1999
DOI: 10.1191/096973399677350269
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality Among Institutionalized Elderly Patients with Dementia

Abstract: The subject of sexuality among elderly patients with dementia was examined, focusing on two main aspects: the sexual behaviour of institutionalized elderly people with dementia; and the reactions of other patients, staff and family members to this behaviour. The behaviour was found to be mostly heterosexual and ranged from love and caring to romance and outright eroticism. Reactions varied, being accepting of love and care but often objecting to erotic behaviour. Understanding of the sexual needs of elderly pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(82 citation statements)
references
References 0 publications
3
78
1
Order By: Relevance
“…If we take the median of all estimates to date, together representative of diverse care settings, the overall prevalence of improper sexual behaviors in dementia is about 6%. A majority (66.7%) of our subjects with disinhibited behaviors were male, replicating prior observation that most subjects ( 1 90%) manifesting 'in-appropriate sexual behaviors' were men [18] , while two others did not find gender differences [1,17] . We did not find age to be associated with improper sexual behaviors, consistent with an earlier report of a community-based survey [1] .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…If we take the median of all estimates to date, together representative of diverse care settings, the overall prevalence of improper sexual behaviors in dementia is about 6%. A majority (66.7%) of our subjects with disinhibited behaviors were male, replicating prior observation that most subjects ( 1 90%) manifesting 'in-appropriate sexual behaviors' were men [18] , while two others did not find gender differences [1,17] . We did not find age to be associated with improper sexual behaviors, consistent with an earlier report of a community-based survey [1] .…”
Section: Discussionsupporting
confidence: 68%
“…One group reported that 54% of their 41 subjects (primarily disinhibited) had vascular dementia, 22% had AD and 9.8% a mild cognitive syndrome [28] . In the study most comparable to ours (because it examined phenomenological distinctions) association with dementia type was not examined [18] . Thus, our data may reasonably be considered the first evidence that the form of improper sexual behavior may differ according to the type of dementia suffered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This human need for intimacy, for touch, hugs and kisses and the desire to feel connected to others does not diminish with age. Yet, aspects of closeness, intimacy or even sexuality are often overlooked in discussions about the well-being of clients with dementia in hospital or care settings [11,18]. People with dementia have the same psychosocial needs as other individuals: "They need stimulation and companionship, they need to feel secure, to feel they are unique and valued individuals, and to feel a sense of self-esteem" [3].…”
Section: Need For Self-disclosure Intimacy and Relationships To Othersmentioning
confidence: 99%